Pengaruh Harga dan Promosi Terhadap Kepuasan Konsumen Toko Bunga di Kota Palembang - Lauwson, Maria Angel; Megawati, Megawati (MDP Student Conference, 2024)
The purpose of this study was to analyze the price and promotion that affect consumer satisfaction of flower shops in Palembang city, and to find out the price and promotion that affect consumer satisfaction in Palembang city. Collecting data in this study by distributing questionnaires to 100 respondents. Sampling using non probability sampling with purposive sampling method with the help of SPSS 25. Partial test results show that price and promotion have a significant positive effect on customer satisfaction with a value of 0.000 <0.050. The simultaneous test proved 95,868 with a significant value of 0.000, which means that the price and promotion variables have a positive and significant effect on customer satisfaction.